농림어업인 삶의 질 향상 및 농산어촌 지역개발 기본계획(’05∼’09) 중간평가 - 박대식 (한국농촌경제연구원, 2008)
The main purposes of this study are as follows: 1) to identify the actual results and problems of the Five-Year(’05∼’09) Plan for Improving Rural Quality of Life; 2) to suggest policy improvement measures; 3) to evaluate the rural impact of the plan; 4) to estimate the target figure of major indicators. The major research methods were the collection and analysis of existing data, interview, and so on. Existing related data were collected by searching the data of related research institutes and governmental organizations. Descriptive statistics such as frequencies, percentage, mean were used to organize and summarize the data. From 2005 to 2007, 132 policy tasks have been propelled. The major aims of the plan were attained enough from the side of investment and evaluation indicators. Also, the plan was evaluated good enough from the side of policy formation, policy execution, and policy result. The rural impact of the plan, on the whole, was positive. In the subjective measurement of rural quality of life, the proportion of positive evaluation increased. In the objective measurement of rural quality of life, however, the bi-polarization of rural society has deepened. New directions of the plan are ① sustainable rural development, ② active rural welfare, ③ differentiation strategy by rural type, and ④ magnification of originality and efficiency. Major policy tasks for improving rural quality of life are ① integration of dual special laws, ② enlargement of legal objects, ③ activation of the committee, ④ activation of secretariat bureau's function, ⑤ conversion of planning system, ⑥ introduction of rural proofing, ⑦ improvement of tasks transferred at region, ⑧ reorganization of task territory, ⑨ improvement of major tasks, and ⑩ excavation of new policy tasks. Researchers: Dae-Shik Park, Mi-Ryung Song, Ju-Young Park Research Period: 2008.2.∼2008.5. E-mail Address: pds8382@krei.re.kr